A Analisis Sikap Gotong Royong Peserta Didik Kelas II SDN Sambirejo 02 Semarang - LAILI NUR HIDAYATUL LATIFAH IMAM SUKANDAR (LPPM STKIP PGRI Sidoarjo, 2023)
This study aims to describe the mutual cooperation attitude of class II student at SDN Sambirejo 02 Semarang. This is mostly due to technological advances so that students tend to be individualistic. So with the following activities : Class pikets, Group Assignments, Clean Fridays foster an attitude of mutual cooperation on Class II students at SDN Sambirejo 02 Semarang. In accordance with the objective of the Regulation of the Minister of Education and culture, gotong royong is one of the character education program in school. This research method is descriptive qualitative. The subjects of this study were class II students at SDN Sambirejo 02 Semarang, titaling 26 students. Data collection in this study was carried out by interview techniques. Data analysis techniques use data reduction and data verification. The result of this study indicate that the attitide of mutual cooperation in class II students at SDN Sambirejo 02 Semarang has been implemented with various actibities such as : Class Pikets, Group Assignments and Clean Friday. In addition, the mutual cooperation attitude is also implemented in Civics, SBdP, and Indonesian subjects.